The use of acellular dermal matrix in palatoplasty to decrease the rate of postoperative oronasal fistula - Abdullah Essam Kattan; Mohammed Abdulghafour; Banderi Abdullah Ahmed; Adnan Ghazi Gelidan; Taghreed Riayd Alhumsi (Journal of the Pakistan Medical Association, 2022)
Different cleft palate repair techniques have been described to achieve optimum results and minimise complications. Postoperative fistulae are one of the most challenging complications after palate repair. In this clinical study, we reviewed the records of patients who underwent palatoplasty using acellular dermal matrix (ADM) as an addition to facilitate difficult cleft palate and palatal fistula closure. It was a retrospective, comparative, single-centre study, in which records of patients who underwent cleft palate surgeries between 2015 and 2018 were reviewed. Patients who underwent cleft palate or palatal fistula repair with and without ADM were included. Fischer’s exact test was used to compare the two groups (primary cleft palate repair with and without ADM) in relation to the rate of fistula occurrence postoperatively. Continuous...